Effectiveness of Nanobubble Technology with Gas Variations in Improving the Quality of Vetiver Wastewater and River Water - Asep Yusuf; Mochamad Anfasa Nurrachman; Muhammad Achirul Nanda; Chay Asdak (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Improving the quality of wastewater and river water is a critical priority for environmental conservation. Vetiver root wastewater and water from the Citepus River in the Cikamiri sub-watershed, Garut Regency, have the potential to cause pollution that affects water quality and local ecosystems. This study evaluated different gases (air, oxygen, and ozone) during the application of nanobubble technology to improve the quality of vetiver root wastewater and Citepus River water in the Cikamiri sub-watershed. Parameters measured were DO, pH, and TDS before and during 15-minute nanobubble treatment. Results showed that oxygen and ozone gases significantly increased DO content of the wastewater and river water. In addition, ozone gas improved pH in river water, and decreased TDS most effectively with ozone. It was concluded that nanobubble technology has potential for enhancing wastewater treatment and river conservation.